2000
DOI: 10.1243/0957650001538245
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the droplet size distribution in a low-pressure steam turbine

Abstract: Realization of numerous tests on the droplet size measurement with extinction probe, in a 200 MW low-pressure steam turbine, provides necessary experimental data for testing the theoretical models of the droplet nucleation process in steam turbines. The earlier computational model accounting for the unsteady and viscous effects given by Bakhtar and Heaton and by Guha and Young, where the steam particles follow randomly chosen different streamlines within the blade rows with prescribed polytropic efficiency dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 2 publications
(3 reference statements)
0
23
0
Order By: Relevance
“…Steady codes are generally not able to predict the poly-dispersed droplet spectra and the average radius typically measured in the rear stages of steam turbines, and therefore, they cannot provide a good assessment of the losses in these stages. References [40][41][42][43] showed that the effect of unsteadiness due to the interaction of blade wakes with downstream blade rows is to broaden significantly the droplet-size distribution giving a shape and a mean diameter closer to the experimental measurements in real turbines. The authors use a statistical approach to account for the temperature fluctuations produced by the flow unsteadiness and showed very good agreements with measurements.…”
Section: Numerical Analyses Of Relaxation Processes In Lp Flowsmentioning
confidence: 99%
“…Steady codes are generally not able to predict the poly-dispersed droplet spectra and the average radius typically measured in the rear stages of steam turbines, and therefore, they cannot provide a good assessment of the losses in these stages. References [40][41][42][43] showed that the effect of unsteadiness due to the interaction of blade wakes with downstream blade rows is to broaden significantly the droplet-size distribution giving a shape and a mean diameter closer to the experimental measurements in real turbines. The authors use a statistical approach to account for the temperature fluctuations produced by the flow unsteadiness and showed very good agreements with measurements.…”
Section: Numerical Analyses Of Relaxation Processes In Lp Flowsmentioning
confidence: 99%
“…The droplet size spectra were found to be broadened by the unsteadiness, and the results predicted a slight bi-modality in the distributions, consistent with optical measurements. 5 Applying a similar method to a 200 MW low-pressure (LP) turbine, Petr and Kolovratnik 6 made comparisons with optical droplet size data, and by tuning the pitch-wise loss profiles, the computed spectra showed respectable agreement with the light extinction measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The surface tension σ = σ(T ) is corrected by the parameter β according to Petr and Kolovratník [2] to match correctly the start of nucleation. The Figures 1 and 2 show the effect of this correction on pressure distribution and wetness respectively for the flow in the Barschdorf nozzle (more information about Barschdorf nozzle problem see in the section ).…”
Section: Model Of Condensing Steam Flowmentioning
confidence: 99%
“…Presented flow model relies on classical nucleation theory of Becker and Doering [1], which is complemented by certain empirical correction. We use the correction for surface tension proposed by Petr and Kolovratnik [2]. Droplets dispersed in elemental volume (from the point of view of used domain discretization -detail are explained in the section about method of solution) have different sizes.…”
Section: Introductionmentioning
confidence: 99%